Micro-Retirement Among Generation Z: A Conceptual Framework For Understanding Periodic Career Interruption As An Alternative Life-Work Integration Strategy - Supriadi, Supriadi (Jurnal Fokus Manajemen, 2024)
This study aims to introduce and theoretically examine the phenomenon of “micro-retirement” among Generation Z, defined as a career management strategy that involves taking periodic unpaid career breaks throughout one’s working life, rather than deferring personal fulfilment until traditional retirement. This conceptual study synthesizes literature on career development, generational studies, and work-life integration. The theoretical framework draws upon life course theory, career construction theory, and work-life boundary theory to conceptualize micro-retirement as a career strategy with distinct antecedents, manifestations, and consequences. The findings suggest that micro-retirement is a multidimensional phenomenon encompassing periodic disengagement from work, experiential prioritization, and financial-temporal optimization. A theoretical model is presented that links generational values, economic realities, and career development needs as drivers of adopting this strategy. Micro-retirement is positioned both as a response to the inadequacies of conventional career models and as a proactive strategy for achieving sustainable work-life integration. The main limitation of this study lies in the need for empirical validation across different contexts and cultures, as well as further exploration of its long-term impacts on careers and financial well-being. This research contributes theoretically to the fields of career development, youth generational studies, and organizational human resource management by encouraging a redefinition of career success and more flexible talent retention strategies aligned with the aspirations of Generation Z.